2000
DOI: 10.1152/jn.2000.84.3.1519
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Spike Backpropagation Generates Burst Discharge in a Sensory Neuron

Abstract: Backpropagating dendritic Na(+) spikes generate a depolarizing afterpotential (DAP) at the soma of pyramidal cells in the electrosensory lateral line lobe (ELL) of weakly electric fish. Repetitive spike discharge is associated with a progressive depolarizing shift in somatic spike afterpotentials that eventually triggers a high-frequency spike doublet and subsequent burst afterhyperpolarization (bAHP). The rhythmic generation of a spike doublet and bAHP groups spike discharge into an oscillatory burst pattern.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(128 citation statements)
references
References 61 publications
6
121
1
Order By: Relevance
“…Indeed, bursting in ELL pyramidal neurons is intrinsic and relies on a somatodendritic interaction (Turner et al 1994;Lemon and Turner 2000). Somatic action potentials back-propagate into the proximal apical dendrites where they trigger a dendritic spike that propagates back to the soma, leading to a depolarizing afterpotential (DAP) and promotes the firing of another somatic action potential.…”
Section: Modeling Differences In Burst Coding Seen In Vitro and In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, bursting in ELL pyramidal neurons is intrinsic and relies on a somatodendritic interaction (Turner et al 1994;Lemon and Turner 2000). Somatic action potentials back-propagate into the proximal apical dendrites where they trigger a dendritic spike that propagates back to the soma, leading to a depolarizing afterpotential (DAP) and promotes the firing of another somatic action potential.…”
Section: Modeling Differences In Burst Coding Seen In Vitro and In Vivomentioning
confidence: 99%
“…Somatic action potentials back-propagate into the proximal apical dendrites where they trigger a dendritic spike that propagates back to the soma, leading to a depolarizing afterpotential (DAP) and promotes the firing of another somatic action potential. This DAP grows in size throughout the burst, which leads to a progressive depolarization and a shortening of the inter-spike interval (ISI) throughout the burst (Lemon and Turner 2000). The burst terminates with a characteristic doublet when the ISI becomes shorter than the dendritic refractory period (Noonan et al 2003), which leads to dendritic failure characterized by the absence of a dendritic spike and terminates the burst.…”
Section: Modeling Differences In Burst Coding Seen In Vitro and In Vivomentioning
confidence: 99%
“…Pyramidal cells have a well-characterized intrinsic burst mechanism that relies on a somatodendritic interaction (Fernandez et al, 2005b;Lemon and Turner, 2000). Burst firing is driven by a depolarizing afterpotential (DAP) generated by current flowing back to the soma from actively back-propagating dendritic Na + spikes.…”
Section: Regulation Of Pyramidal Cell Burstingmentioning
confidence: 99%
“…It has been shown that the DAP is generated within a few ms after an action potential is initiated. 22,23 The amplitude of the DAP is expressed either as percentage of the peak of the CAP amplitude or in absolute value (mV).…”
Section: Isolation Of Spinal Cordmentioning
confidence: 99%